2001
DOI: 10.1007/s100960100574
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of an Automated System Using Selected Bacteria That Harbor Challenging and Clinically Relevant Mechanisms of Resistance to Antibiotics

Abstract: A multicenter study was carried out to evaluate the performance of a new commercial automated system in comparison with that of the reference agar dilution method. Ten clinical microbiology laboratories tested a collection of 61 strains of gram-negative bacilli (49 Enterobacteriaceae and 12 Pseudomonas aeruginosa), and 6 other laboratories tested a collection of 55 strains of gram-positive cocci (10 enterococci and 45 staphylococci) against 10-20 antimicrobial agents. The strains were selected on the basis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Barry et al (24) found VITEK 2 results to be consistent with routine resistance tests at a rate of 96.5%, 96.7%, and 95.9%, respectively, for staphylococci, enterococci, and gram-negative bacilli. Canton et al (25) found the VITEK 2 method less reliable than the microdiffusion method, whereas Leclercq et al (26) stated that VITEK 2 was more reliable than the agar dilution method. According to Nyberg et al (27), sensitivity and specificity vary in different studies, but high sensitivity and specificity have been achieved with VITEK 2 when testing K. pneumoniae isolates (15,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Barry et al (24) found VITEK 2 results to be consistent with routine resistance tests at a rate of 96.5%, 96.7%, and 95.9%, respectively, for staphylococci, enterococci, and gram-negative bacilli. Canton et al (25) found the VITEK 2 method less reliable than the microdiffusion method, whereas Leclercq et al (26) stated that VITEK 2 was more reliable than the agar dilution method. According to Nyberg et al (27), sensitivity and specificity vary in different studies, but high sensitivity and specificity have been achieved with VITEK 2 when testing K. pneumoniae isolates (15,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Limited comparison with MICs determined by Etests was, however, undertaken here, and a fuller comparison of MICs obtained by the VITEK 2 with reference MIC data is published elsewhere. 5,6 By recording and interpreting phenotypes the VITEK 2 AES accurately inferred the presence or absence of mecAmediated methicillin resistance in staphylococci; VanA-, VanB-or VanC-mediated glycopeptide resistance in enterococci; gyrA-and parC-mediated quinolone resistance in staphylococci and Enterobacteriaceae; AAC(6Ј)-APH(2Љ)-mediated gentamicin resistance in enterococci and staphylococci; erm-mediated macrolide resistance in pneumococci; ESBL-mediated cephalosporin resistance in Enterobacteriaceae and P. aeruginosa; and acquired penicillinases in Enterobacteriaceae. Enterococci with the VanA, VanB and VanC determinants were distinguished reliably.…”
Section: Discussionmentioning
confidence: 99%
“…The VITEK 2 is an automated susceptibility testing system enabling rapid (4-7 h) determination of MICs by the analysis of growth kinetics of bacteria with antibiotics in test cards. [5][6][7] The AES provides standardized interpretive reading of these MICs. 8,9 Briefly, it comprises a database of MIC distribution for different combinations of antibiotics and prevalent resistance mechanisms in different species, together with a series of algorithms.…”
Section: Introductionmentioning
confidence: 99%